Comparison and lessons learned from neglected tropical diseases and tuberculosis - Alice Wang; Adam MacNeil; Susan Maloney (Public Library of Science (PLoS), 2021)
Currently, tuberculosis (TB) is the leading cause of death from a single infectious agent and accounts for over one-third of all HIV-related deaths. However, research and programmatic funding have lagged far behind investments for many other diseases. For about a century, the current Bacillus Calmette-Guérin vaccine has been the only effective vaccine and is only effective in preventing severe disease in children; the first new therapeutic drug for TB in over 40 years was brought to market a few years ago; and until 10 years ago, diagnosis of TB depended on a century-old testing technique. This paper relates TB to neglected tropical diseases (NTDs) and highlights shared characteristics. The aim is to elevate awareness of TB within the framework of NTDs and gain insights from successes in addressing NTDs and how these lessons can be applied to help global health programs change the trajectory of the TB epidemic. A literature review was conducted to compare TB to NTDs and highlight lessons learned from NTD control that can be applied to the TB epidemic. Common features of NTDs include underlying burden of disease, influence and effect on poverty and development, and neglect through political will and funding. There are overarching principles for the design and implementation of NTD control programs that could be applied to ending TB.